Use of Physical Education Classes as a Didactic Laboratory for Teaching Affine Function - Cavalcante da Silva, Kleber Alexandre; Farias, Valcir João da Cunha; Souza de Almeida, Carmem Lucia Brito (International Journal of Advanced Engineering Research and Science, 2022)
The objective of this article was to present an alternative way to teach mathematics, more specifically the affine function. In this research, Physical Education classes were used as a Didactic Laboratory for Mathematics classes, where from athletics tests, 100 and 400 meters races, basic concepts such as graph construction and calculation of coefficients are carried out. Also, an analysis is made if the interdisciplinarity presented reaches some of the objectives required for the use of a Didactic Laboratory. During the research, the students were divided into groups to solve the proposed problem based on data obtained through measurements of the athletics events carried out by the students themselves, with this, they had the opportunity to produce arguments and answers in a significant way. for the questions emanating from the study of affine function. The results showed that there was a good absorption of the content and performing an average comparison between the students of the class participating in the experiment with students of classes that did not participate, a higher average of the participants was observed, a difference of 19.3%.